Willingness to pay for and willingness to vaccinate with the COVID-19 vaccine booster dose in China - Zhou, Hui Jun; Pan, Lei; Shi, Hui; Luo, Ji Wei; Wang, Pei; Porter, Hannah K.; Bi, Ye; Li, Minghui (Frontiers in Pharmacology, 2022)
Objective: The present study aims to assess the willingness to pay (WTP) for and willingness to vaccinate (WTV) with the Coronavirus (COVID-19) vaccine booster dose in China when the pandemic is under adequate control and the majority of the population is vaccinated. This study is also to identify significant factors associated with the WTP. Methods: This was a cross-sectional study on adults with no past or present COVID-19 infection. An online questionnaire was distributed to collect data on vaccination status, quarantine experience, and factors related to health beliefs on vaccination. The WTV was assessed through the vaccination preference. The WTP was examined by payment scale (PS) and iterative bidding game (IBG) administered in random order. Three IBG algorithms with different starting-price were presented randomly. The average WTP of PS and IBG were analyzed as primary outcomes using univariate and multivariate analyses. Multivariate ordered logistic regression was performed to identify significant factors for the WTP. Results: The survey recruited 543 participants with a mean age of 32 years and 57.80% being female. The WTV rate was 86.74%, while 94.66% of participants completed full-schedule or enhanced vaccination. The mean WTP was CNY149 (±CNY197) and the median WTP was CNY80. Regarding significant factors for the WTP, urban residents were 57% more likely (95% CI: 1.11-2.22) to pay for a high-priced vaccine than rural residents. Respondents who completed full-schedule vaccination were 46% more likely (95% CI: 1.03-2.07) to pay for a high-priced vaccine than those who completed enhanced vaccination. Respondents with a low household income of CNY40k or lower were 62% less likely (95% CI: 0.21-0.66) to pay for a high-priced vaccine than those with a middle household income of CNY110k-210k. Other significant factors associated with the WTP included the perceived benefit of vaccination and peer environmental pressure in the health belief model. Conclusion: The WTV with the COVID-19 vaccine booster dose was high in China. The WTP was influenced by the place of residence, vaccination status, household income, perceived benefit of vaccination, and environmental peer pressure. Study findings can inform policymakers to better design vaccination programs and financial schemes involving out-of-pocket payments.